Mapping impurity of single-walled carbon nanotubes in bulk samples with multiplex coherent anti-Stokes Raman microscopy - Duarte, Alex S.; Rehbinder, Jean; Correia, Ricardo R. B.; Buckup, Tiago; Motzkus, Marcus (Nano letters, 2013)
Mapping of defects in bulk samples of single-walled carbon nanotubes (SWNT) is performed via multiplex coherent anti-Stokes Raman microscopy. The D and G vibrational bands are acquired simultaneously, and their relative amplitude is used as a criterion to quantify the local purity in spin-coated SWNT samples. We observe that defects induced by oxidation are related to the spatial dispersion of nanotubes in a solid distribution.